Exploring First-Time Parents' Experiences of the Transition to Parenthood: A Qualitative Study in Indonesia - Machfudloh Machfudloh; Andari Wuri Astuti; Endang Koni Suryaningsih (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: cceptance of being a parent is an important life event and becomes challenging to adjust for many people, particularly for first-time parents. Acceptance of being a parent could potentially affect a person’s psychological level in the rate of occurrence of stress, depression, violence against family children, and even divorce has an increasing trend. Subjects and Method: This study employed a qualitative design using phenomenology approach. The research subjects involved of five couples (husbands and wives) who had their first child aged between 3-6 months, two midwives from the Independent Midwife Practice in Demak Regency, Central Java. The technique for selecting sample were purposive sampling and snowball. The analysis used the interactive analysis model developed by Miles and Huberman. Results: Three main themes emerged, which were: the concept of becoming parents, the process of adapting to the transition to parenthood, and hope. Couples who are new parents of children aged 3-6 months have limited knowledge about their roles and responsibilities. They were unprepared to carry out their rights and obligations of being parents, and lack preparation for the transition to parenthood, which subsequently create conflicts/problems in the family. Sources of support for new parents include spouses, immediate family members, community resources, and health workers. Conclusion: Limited knowledge and unpreparedness to be parents would potentially lead to negative affect on the welfare of new parents. Providing marriage guidance, family assistance, and education on parenthood preparation can increase the knowledge, skills, and readiness of couples in the transition to parenthood during the prenatal and postnatal period.